Comparative pharmacokinetic analysis of raw and steamed Panax notoginseng roots in rats by UPLC-MS/MS for simultaneously quantifying seven saponins - Jiajia Dong; Zhenzhen Yin; Lianlin Su; Mengting Yu; Meng Wang; Lin Li; Chunqin Mao; Tulin Lu (Taylor & Francis Group, 2021)
Context After being steamed, the restorative effects of Panax notoginseng (Burk.) F. H. Chen (Araliaceae) will be strengthened. However, the underlying mechanism remains elusive. Objective To compare the pharmacokinetics of ginsenosides Rg1, Rb1, Rd, Re, Rg5, Rk1, notoginsenoside R1 (GRg1, GRb1, GRd, GRe, GRg5, GRk1 and NGR1) in the raw and steam-processed P. notoginseng (RPN and SPN). Materials and methods The pharmacokinetics of seven components after oral administration of SPN and RPN extracts (1.0 g/kg) were investigated, respectively, in SD rats (two groups, n = 6) using UPLC-MS/MS. Results The approach elicited good linear regression (r2 > 0.991). The accuracy, precision and stability were all within ± 15%. The extraction recoveries and matrix effects were 75.0-100.8% and 85.1-110.3%, respectively. Compared with the RPN group, AUC0-t of GRg1 (176.63 ± 42.49 ng/h/mL), GRb1 (5094.06 ± 1453.14 ng/h/mL), GRd (1396.89 ± 595.14 ng/h/mL), and NGR1 (135.95 ± 54.32 ng/h/mL), along with Cmax of GRg1 (17.41 ± 5.43 ng/mL), GRb1 (361.48 ± 165.57 ng/mL), GRd (62.47 ± 33.65 ng/mL) and NGR1 (23.97 ± 16.77 ng/mL) decreased remarkably with oral administration of the SPN extracts, while GRe showed no significantly difference. Of note, GRg5 and GRk1 could not be detected in the plasma. Conclusions Influence of the processing reduced the systemic exposure levels to GRg1, GRb1, GRd and NGR1. It is the first report of comparative pharmacokinetic study of multiple saponins analysis after oral administration of RPN and SPN extract, which might be helpful for further studies on its steam-processing mechanism.